Improving Students’ Reading Comprehension By Using the Orthographic Method for Elementary Students’ - Armelia, Nanda; Isnaniah, Isnaniah; Nuraini, Hery (Jurnal Basicedu, 2024)
Unfortunately, many people experience reading difficulties, affecting their educational attainment and overall quality of life. Addressing this challenge has been a focus of researchers, educators and policymakers for decades. This research aims to determine the impact of the orthographic method on the development of reading comprehension in grade 4 students. The research design used was a pre-experimental method with a pre-test and post-test research design. Researchers used quantitative research methods with a pre-experimental planning strategy to determine the influence of the Orthographic Method on students' inspiration to learn English comprehension. A total of 40 sample students were selected as the sample for this research. The main components of data collection techniques are tests that are used to evaluate students' progress towards learning goals and their abilities can be seen as an evaluation tool in this context. The researchers used a research method called one-group pre-tested posttest design and compared the differences between the pretest and posttest. The results of this research there is a significant improvement in teaching using the orthographic method on students' reading comprehension in test subjects. This means that the Orthographic method activates students' existing knowledge about the topic, provides opportunities for the topic and gives students the opportunity to engage with the topic